The visual arts teaching curriculum in Paraná: the interferences proposed by regulation on teacher formation and performance (Palíndromo, 2015)
In this paper, aiming at identifying the intrinsic relationship between tea- cher education and performance, as well as the asymmetries between the curri- cular proposals and the construction of a new teacher profile and teaching ar- ticulated visual arts to the demands of contemporary times, analyzed in the li- ght of historical materialism-dialético, data on Degrees in the state of Paraná Visual Arts. These data come from the master’s research and postdoctoral of the authors, both held by Post-Program Degree in Visual Arts of the State of San- ta Catarina. From qualitative and quanti- tative methodology, based on Creswell (2010) mapped the amount and location of degrees in Parana noting that meet the educational demands of Art discipline in basic education remains short of actual needs. We identify further that only 50% of the courses are in line, fully, with gui- ding documents and laws that interfere with these curriculum. Such theoretical and methodological perspective indica- ted that teacher training-acting is per- meated by the principles of socio-eco- nomic and political order that permeate the contemporary educational practice.
Keywords: education and action of teachers; visual arts; Paraná